Handbook of Optimization in Medicine - Romeijn, H. Edwin.; Pardalos, Panos M. (Springer Optimization and Its Applications, 2009)
Handbook of Optimization in Medicine is devoted to examining the dramatic increase in the application of effective optimization techniques to the delivery of health care. The articles, written by experts from the areas of optimization (operations research), computer science, and medicine, focus on models and algorithms that have led to more efficient and sophisticated treatments of patients. Topics covered include: * optimization in medical imaging, * classification and data mining with medical applications, * treatment of epilepsy and other brain disorders, * treatment of head-and-neck, prostate, and other cancers using conventional conformal and intensity-modulated radiation therapy as well as proton therapy, * treatment selection for breast cancer based on new classification schemes, * optimization for the genome project, *optimal timing of organ transplants. This handbook is an invaluable resource for graduate students and academic researchers in biomedical engineering, computer science, operations research, and medicine. Practioners as well will be able to adapt the different approaches to their needs.